Fdi and Its Impact on Indian Economy: An empirical analysis of the impact of FDI on the Indian economy (Journal of Advances and Scholarly Researches in Allied Education, 2011)
The present study attempts toempirically examine the impact of Foreign Direct Investment (FDI) equityinflows on Indian economy over the period of April 2005 to March 2011, before andafter the eruption of Global Financial Crisis. The study explains the linkagesbetween FDI equity inflows and macro-economic variables such as Inflation,Index of Industrial Production (IIP), interest rates, exchange rates andforeign exchange reserves. The empirical results indicate that GDP, inflationand Trade Openness are important factors in attracting FDI inflows in India during post-reform period whereas ForeignExchange Reserves are not important factors in explaining FDI inflows in India.